Comparison of irrigation performance based on management and cropping types - Ayana, Essayas K.; Awulachew, Seleshi Bekele (2008)
Although performance evaluation of irrigated agriculture has gained momentum since late 1980s worldwide such attempt is rarely carried out in Ethiopia. The aim of this study was to assess the performance of 7 irrigation schemes some of which are expected to contribute much to the national economy. Sugar cane is grown by three of these schemes whereas cotton is grown by three schemes and the remaining single scheme grows tobacco. With regards to management types both government agency and community managed schemes are considered. The scheme level values of water supply performance indicators show that there was no constraint of water availability and supply at scheme level. In general, schemes that grow sugar cane were found to have attained higher outputs per units of land and water used which ranges from 7794 ? 10834US$/ha and 0.24 ? 0.55 US$/m3 respectively. On the other hand, whether state farm or community managed, schemes that grow cotton have shown low output per units of land and water, i.e. 310 ? 385 US$/ha and 0.01 ? 0.05 US$/m3 respectively. Large productivity performance differences have been observed between irrigation schemes with same cropping and management types. From scheme level performance values it is not simple to identify the area where and what is going wrong which is responsible for low performance. Generally, problems casing low productivity derive both in management and deterioration of physical structures. Hence investment on improvements of physical structures, management and operation of the system at all levels will bring substantial improvement in the performances of cotton producing schemes.